Spreading depolarizations trigger caveolin‐1–dependent endothelial transcytosis. Issue 3 (24th September 2018) - Sadeghian, Homa; Lacoste, Baptiste; Qin, Tao; Toussay, Xavier; Rosa, Roberto; Oka, Fumiaki; Chung, David Y.; Takizawa, Tsubasa; Gu, Chenghua; Ayata, Cenk
Abstract : Objective: Cortical spreading depolarizations (CSDs) are intense and ubiquitous depolarization waves relevant for the pathophysiology of migraine and brain injury. CSDs disrupt the blood–brain barrier (BBB), but the mechanisms are unknown. Methods: A total of six CSDs were evoked over 1 hour by topical application of 300 mM of KCl or optogenetically with 470 nm (blue) LED over the right hemisphere in anesthetized mice (C57BL/6 J wild type, Thy1‐ChR2‐YFP line 18, and cav‐1 –/– ). BBB disruption was assessed by Evans blue (2% EB, 3 ml/kg, intra‐arterial) or dextran (200 mg/kg, fluorescein, 70, 000 MW, intra‐arterial) extravasation in parietotemporal cortex at 3 to 24 hours after CSD. Endothelial cell ultrastructure was examined using transmission electron microscopy 0 to 24 hours after the same CSD protocol in order to assess vesicular trafficking, endothelial tight junctions, and pericyte integrity. Mice were treated with vehicle, isoform nonselective rho‐associated kinase (ROCK) inhibitor fasudil (10 mg/kg, intraperitoneally 30 minutes before CSD), or ROCK‐2 selective inhibitor KD025 (200 mg/kg, per oral twice‐daily for 5 doses before CSD). Results: We show that CSD‐induced BBB opening to water and large molecules is mediated by increased endothelial transcytosis starting between 3 and 6 hours and lasting approximately 24 hours. Endothelial tight junctions, pericytes, and basement membrane remain preserved after CSDs. Moreover, we show that CSD‐induced BBB disruption is exclusively caveolin‐1–dependent and requires rho‐kinase 2 activity. Importantly, hyperoxia failed to prevent CSD‐induced BBB breakdown, suggesting that the latter is independent of tissue hypoxia. Interpretation: Our data elucidate the mechanisms by which CSDs lead to transient BBB disruption, with diagnostic and therapeutic implications for migraine and brain injury.